2009
DOI: 10.1187/cbe.09-02-0011
|View full text |Cite
|
Sign up to set email alerts
|

An Investigative, Cooperative Learning Approach to the General Microbiology Laboratory

Abstract: Investigative-and cooperative-based learning strategies have been used effectively in a variety of classrooms to enhance student learning and engagement. In the General Microbiology laboratory for juniors and seniors at James Madison University, these strategies were combined to make a semester-long, investigative, cooperative learning experience involving culture and identification of microbial isolates that the students obtained from various environments. To assess whether this strategy was successful, stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
2
12
0
3
Order By: Relevance
“…[30] Another study conducted by Alexander et al (2008) mentioned that, peer learning encourages students to cooperate with each other, to promote students help, assist, support, encourage and praise their peers. [31] Moreover, this is in agreement with the study done by Seifert et al (2009), their results showed that, nursing students had higher preference for cooperative learning strategies after practicing them in class. [32] The present study revealed that all students (100%) in the intervention group were satisfied with peer learning.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…[30] Another study conducted by Alexander et al (2008) mentioned that, peer learning encourages students to cooperate with each other, to promote students help, assist, support, encourage and praise their peers. [31] Moreover, this is in agreement with the study done by Seifert et al (2009), their results showed that, nursing students had higher preference for cooperative learning strategies after practicing them in class. [32] The present study revealed that all students (100%) in the intervention group were satisfied with peer learning.…”
Section: Discussionsupporting
confidence: 81%
“…[31] Moreover, this is in agreement with the study done by Seifert et al (2009), their results showed that, nursing students had higher preference for cooperative learning strategies after practicing them in class. [32] The present study revealed that all students (100%) in the intervention group were satisfied with peer learning. while only 10% of the students in the control group.…”
Section: Discussionsupporting
confidence: 81%
“…This approach was not intended to be a substitute for classroom pedagogies that have been demonstrated to be effective in the instruc tion of microbiology, such as active learning, collaborative learning, and inquirybased and problembased learning (Seifert et al, 2009;Southwick et al, 2010). This approach nicely complemented what was already being done in the microbiology classroom at Drake Uni versity, utilizing microbial diversity as a unifying theme in an attempt to increase student interest, enhance learning, and increase retention of course content.…”
mentioning
confidence: 90%
“…It provided students with immense benefits over traditional laboratory experiences, and even over inquiry-based laboratory experiences (Weaver et al ., 2008; Brownell et al ., 2012). Many derivatives and hybrids have originated from the three approaches, such as guided-inquiry learning (Spiro and Knisely, 2008) and investigative and cooperative learning (Seifert et al ., 2009), as well as integrated teaching and research (Kloser et al ., 2011). These approaches offer varying levels and forms of autonomy supports for students’ cognitive engagement and learning motivation.…”
Section: Introductionmentioning
confidence: 99%